Dampak Konseling Kelompok Teknik Cognitive Restructuring Terhadap Resiliensi Akademik - Amelia Masdelina; Arifin Nur Budiono; Fakhruddin Mutakin (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
Students with low academic resilience are influenced by factors of belief in their abilities, the ability to do things well, manage anxiety, and the ability to complete all demands. Based on preliminary studies, It demonstrates that low academic resilience students require assistance in order to become resilient throughout the academic process. Cognitive restructuring methods were used in the group counseling services that were provided as part of the assistance.. The purpose of this study was to examine the impact of cognitive restructuring technique group counseling on the academic resilience of students at SMK IBU Pakusari in the MM major. Respondents who were examined were 372 students with samples taken by 4 students by purposive sampling. Quantitative experiments using a pretest-posttest design with just one group is used in this type of study. This study's methods for gathering data include using a questionnaire. The outcomes demonstrated that the t table's results were: 5.702 > 3.182 at a significance level of 5% (df = 3 n = 4). The findings demonstrated that cognitive restructuring-based group counseling services improved students' academic resilience Keywords:Â  Group Counseling;Cognitive restructuring technique; academic resilience